This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can write this sum as:
∑ n = 1 ∞ ( n ( n + 1 ) ) 2 2 n + 1 = ∑ n = 1 ∞ n 2 ( n + 1 ) 2 ( n + 1 ) 2 − n 2 = ∑ n = 1 ∞ n 2 1 − ( n + 1 ) 2 1 .
This sum telescopes (i.e. successive terms all cancel each other out), with only 1 2 1 = 1 remaining. Hence the sum is 1 , and the answer is None of these .